2019
DOI: 10.1080/24750573.2019.1625184
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of long-term efficacy and safety of blonanserin treatment in individuals with first-episode and relapsed schizophrenia: a 3-year retrospective study

Abstract: Purpose: The objective of this retrospective chart review study was to evaluate the long-term efficacy and tolerability of blonanserin treatment in individuals with schizophrenia. Patients and methods: We collected data from 28 (56%) antipsychotic-naïve subjects with firstepisode (FE) schizophrenia and 22 subjects with relapsed schizophrenia treated with blonanserin. We investigated psychiatric hospitalization and medication discontinuation rates, Positive and Negative Syndrome Scale (PANSS) scores, Clinical G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Blonanserin induced improvement in the negative symptoms and cognitive impairment with less adverse eff ects in various short and long term studies [28]. It has been shown that cognition improvement more than 0.5 SD improves quality of life [29].…”
Section: Discussionmentioning
confidence: 99%
“…Blonanserin induced improvement in the negative symptoms and cognitive impairment with less adverse eff ects in various short and long term studies [28]. It has been shown that cognition improvement more than 0.5 SD improves quality of life [29].…”
Section: Discussionmentioning
confidence: 99%